2018
DOI: 10.3390/app8050659
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Lithium-Ion Battery Modeling Methods for State-of-Charge Estimation in Electrical Vehicles

Abstract: As a critical indictor in the Battery Management System (BMS), State of Charge (SOC) is closely related to the reliable and safe operation of lithium-ion (Li-ion) batteries. Model-based methods are an effective solution for accurate and robust SOC estimation, the performance of which heavily relies on the battery model. This paper mainly focuses on battery modeling methods, which have the potential to be used in a model-based SOC estimation structure. Battery modeling methods are classified into four categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
118
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(145 citation statements)
references
References 71 publications
(93 reference statements)
0
118
0
1
Order By: Relevance
“…The content of model‐based SOC estimation method incorporates of two main parts: application of battery models and appropriate algorithm. The battery model is used to calculate the voltage, current and temperature, and the estimation algorithm evaluates the SOC . At present, there are two kinds of electrical battery models used in SOC estimation, namely, electrochemical model and ECM.…”
Section: Model‐based Bms Applicationmentioning
confidence: 99%
“…The content of model‐based SOC estimation method incorporates of two main parts: application of battery models and appropriate algorithm. The battery model is used to calculate the voltage, current and temperature, and the estimation algorithm evaluates the SOC . At present, there are two kinds of electrical battery models used in SOC estimation, namely, electrochemical model and ECM.…”
Section: Model‐based Bms Applicationmentioning
confidence: 99%
“…The authors showed that increasing the number of equivalent models by more than two brings no benefits as the complexity during parameterization increases along with the estimation error, whereas the EKF cannot overcome this modeling weakness which results in the SoC error becoming increasingly large when using a high-order RC model. Lastly, in [97], authors use a GA to investigate four different modeling approaches of an LFP 10 Ah cell. A crude approximation of the LFP's dynamics is made with a mathematical combined model, a better performance is achieved with a 2nd order ECM, whereas a single-particle model and a data-driven with support vector machine shown the best accuracy but with significantly increased required computational time.…”
Section: Parameter Extraction With Heuristic Optimizationmentioning
confidence: 99%
“…The assumption of 100% rise considered here is taken as a worst case scenario. Based on the objectives of the investigation, the use of various battery models such as empirical models, physico-chemical models and equivalent circuit models is prevalent [33]- [36] in scientific circles. Physico-chemical models are the closest to the underlying electrochemical processes taking place within the cell, whereas the equivalent circuit models, although quite popular in their usage, present a higher degree of abstraction, employing electrical circuit analogies to approximate accuracy [38]- [41].…”
Section: B Battery Systemmentioning
confidence: 99%